Eccrine poroma over the scalp: an atypical presentation - Golwad, Pooja M.; Mahajan, Sunanda A.; Kamble, Pramod D. (International Journal of Research in Dermatology, 2022)
An eccrine poroma is a solitary tumor arising from the eccrine duct epithelium in the epidermis. The lesions commonly occur on palm and soles, and occasionally on the nose, eyelids, neck, and chest. We report a patient who presented with a slow-growing nodular lesion over his scalp, dermoscopic examination showed lobular appearance composed a structureless white areas and pigmentation at periphery with erosion in centre, vascular pattern with interlacing white cords separating structure-less islands with central ulceration. Histopathology examination showed a nodular infiltrate composed of poroid cells extending from epidermis to dermis and finding suggestive of an eccrine poroma. We are presenting this case for its unusual site and early onset of presentation.